2021
DOI: 10.1186/s12885-021-08574-1
|View full text |Cite
|
Sign up to set email alerts
|

The combination of 13N-ammonia and 11C-methionine in differentiation of residual/recurrent pituitary adenoma from the pituitary gland remnant after trans-sphenoidal Adenomectomy

Abstract: Background This study aimed to assess the clinical usefulness of 13N-ammonia and 11C- Methionine (MET) positron emission tomography (PET)/ computed tomography (CT) in the differentiation of residual/recurrent pituitary adenoma (RPA) from the pituitary gland remnant (PGR) after trans-sphenoidal adenomectomy. Methods Between June 2012 and December 2019, a total of 19 patients with a history of trans-sphenoidal adenomectomy before PET/CT scans and his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…11 C-methionine PET (Met-PET) has been established to be beneficial in localizing the entire range of pituitary adenoma subtypes in terms of recurrent and newly diagnosed tumors [53,55,[57][58][59], especially microadenomas [7,55,60]. 11 C-methionine PET makes the most from a substantially lower brain uptake.…”
Section: C-methionine Petmentioning
confidence: 99%
“…11 C-methionine PET (Met-PET) has been established to be beneficial in localizing the entire range of pituitary adenoma subtypes in terms of recurrent and newly diagnosed tumors [53,55,[57][58][59], especially microadenomas [7,55,60]. 11 C-methionine PET makes the most from a substantially lower brain uptake.…”
Section: C-methionine Petmentioning
confidence: 99%
“…Furthermore, [ 11 C]C-MET PET may incorrectly detect PAs. In addition, [ 13 N]N-ammonia ([ 13 N]N-NH3) was found to represent the metabolic integrity of pituitary tissue well [ 9 , 10 ]. In a previous study, we found that [ 13 N]N-NH3 demonstrated a higher uptake in pituitary tissue than in PAs, acting as a good tracer for normal pituitary tissue in patients with PAs [ 11 ].…”
Section: Introductionmentioning
confidence: 99%